Trust, talk and the dictaphone: Tracing the discursive accomplishment of trust in a surgical consultation. (January 2014) - O'Grady, Catherine; Dahm, Maria R; Roger, Peter; Yates, Lynda
Using discourse analytical methods, this article examines the interactional accomplishment of trust. Focusing on a case study drawn from a corpus of 28 surgical consultations collected in a gastro-intestinal clinic, it traces the trust-building process in a specific, communicatively challenging encounter where the patient is seeking a second opinion following an operation that she deems unsuccessful. Discourse analytical findings make visible the doctor's strategic interactional work to build interpersonal trust with the patient and to regain her trust in the surgical profession. This work extends beyond interaction with the patient to include dictation of a letter to the referring doctor in the patient's presence. Close analysis of the encounter reveals how this co-constructed consultation letter is deployed to strengthen the fragile patient–doctor trust engendered thus far. The article therefore provides insights into the discursive processes of trust building that could potentially be of considerable practical relevance to the medical profession.